Shear Bond Strengths between Three Different Yttria-Stabilized Zirconia Dental Materials and Veneering Ceramic and Their Susceptibility to Autoclave Induced Low-Temperature Degradation - Sehgal, Manoti; Bhargava, Akshay; Gupta, Sharad; Gupta, Prateek (International Journal of Biomaterials, 2016)
A study was undertaken to evaluate the effect of artificial aging through steam and thermal treatment as influencing the shear bond strength between three different commercially available zirconia core materials, namely, Upcera, Ziecon, and Cercon, layered with VITA VM9 veneering ceramic using Universal Testing Machine. The mode of failure between zirconia and ceramic was further analyzed as adhesive, cohesive, or mixed using stereomicroscope. X-ray diffraction and SEM (scanning electron microscope) analysis were done to estimate the phase transformation (m-phase fraction) and surface grain size of zirconia particles, respectively. The purpose of this study was to simulate the clinical environment by artificial aging through steam and thermal treatment so as the clinical function and nature of the bond between zirconia and veneering material as in a clinical trial of 15 years could be evaluated.